Intransitive-based Applicatives in Bahasa Indonesia - Mytha Candria; F.X. Sawardi (PAROLE: Journal of Linguistics and Education, 2022)
As there has not been research specifically focused on the meanings of intransitive-based applicatives in bahasa Indonesia, this research was carried out as an effort to uncover the meanings of Indonesian intransitive-based applicative constructions. To reach the goal, we use Dixon’s framework of four broad categorizations of applicative meanings (2012). The research is descriptive and qualitative in nature, and the approach used is that of structural typology. Data were collected using library research, document analysis, and purposive sampling. Intransitive-based applicatives in bahasa Indonesia has four meanings; they, ordered based on the frequency of occurences, are locative, stimulus for a stative verb (G-stimulus), stimulus for corporeal activities (G-corporeal), and comitative. There are, however, -kan intransitive-based applicative constructions that cannot neatly fall into Dixon’s meaning categorization. We then proposed another applicative meaning of -kan, as is suggested by Sneddon et al. (2010). In conclusion, we hold that Dixon’s categorization of applicative meanings is a framework quite exhaustive to understand the semantic elements of Indonesian transitive-based applicatives.